Realtime Laser Beam Steering and Calibration Method for Coherent Biomedical Distance and Motion Sensing - Schmidt, Marius; Sadeghi, Misha; Rahimi, Farnaz; Eskofier, Björn; Buglagil, Arda; Schmauß, Bernhard; Carlowitz, Christian (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
This paper presents a depth camera based 3D position tracking and calibration method for realtime millimeter-accuracy galvanometer laser beam steering that enables high sensitivity coherent optical distance and movement sensing for biomedical applications.
CRIS-Team Scopus Importer:2024-10-04